Aging and health among migrants in a European perspective. Issue 1 (December 2016) - Kristiansen, Maria; Razum, Oliver; Tezcan-Güntekin, Hürrem; Krasnik, Allan
Abstract Population aging and the associated changes in demographic structures and healthcare needs is a key challenge across Europe. Healthy aging strategies focus on ensuring the ability to maintain health, quality of life and independent living at old age. Concurrent to the process of population aging, the demographics of Europe are affected by increased migration resulting in substantial ethnic diversity. In this paper, we narratively review the health profile of the growing proportion of aging migrants in Europe, outline key factors shaping health among this diverse group and consider ways of addressing their healthcare needs. Although factors shaping aging processes are largely similar across populations, migrant-specific risk factors exist. These include exposure to health risks before and during migration; a more disadvantaged socioeconomic position; language barriers and low health literacy; cultural factors influencing health-seeking behaviours; and psychosocial vulnerability and discrimination affecting health and quality of life. Overall, migrants experience the same morbidity and mortality causes as the native populations, but with different relative importance, severity and age of onset and with substantial differences within and between migrant groups. Little is known regarding health behaviours among aging migrants, although differences in cancer screening behaviours have been identified. Indications of widening health differentials between migrants and native populations with age and informal barriers to quality healthcare for aging migrants are causes of concern. In conclusion, there is a need for attention to migration alongside other determinants of healthy aging. The diversity in individual characteristics, life course processes and contextual factors shaping aging processes among migrants point to the need for a sensitive and comprehensive approach to policies, practices and research within the field of healthy aging. This is important to accommodate for the needs of the growing number of aging migrants in Europe and counter inequities in health and well-being at old age.